A computationally efficient model for the cyclic behavior of reinforced concrete structural members. (15th June 2017) - Mourlas, Christos; Papadrakakis, Manolis; Markou, George
Highlights: Accurate modelling of reinforced concrete structures using finite elements. New material algorithm for the realistic simulation of the 3D brittle behavior of concrete under cyclic loading conditions. The material model treats cracking with smeared crack approach including crack opening and crack closure. Numerical accuracy of the proposed method by comparing the numerical results with the corresponding experimental ones. Computational efficiency and robustness of the proposed nonlinear procedure, are demonstrated. Abstract: During the last decades, many researchers have proposed a number of constitutive models for simulating the behavior of reinforced concrete structures under cyclic loading. The finite element analysis, has been used in the past, to produce solutions for specific structural members that undergo different loading conditions. The purpose of this paper is to propose a computationally efficient finite element based numerical method in order to simulate accurately and efficiently the mechanical behavior of a wide range of reinforced concrete structural members under cyclic loading. The proposed method is based on the experimental results and the concrete modeling of Kotsovos and Pavlovic (1995) as modified by Markou and Papadrakakis (2013). A new algorithmic formulation that describes the development of microcracking, macrocracking and the brittle behavior of the concrete under cyclic behavior, is presented. The concrete domain is simulated by 8- and 20-noded hexahedral elements, which treat cracking with the smeared crack approach. Steel reinforcement is modeled with truss and beam elements which are considered embedded inside the hexahedral concrete mesh. The numerical accuracy of the proposed method is demonstrated by comparing the numerically force-deflection curves with the corresponding experimental results found in the literature.